PEMBUATAN POJOK BACA GUNA MENUMBUHKAN MINAT BACA DI DESA KANCANA KECAMATAN CIKIJING KABUPATEN MAJALENGKA - Rahmi Hidayati; Dicky Fauzi Firdaus; Halawati, Firda (Jurnal Pengabdian Kepada Masyarakat, 2024)
Reading is an activity that can expand knowledge. Through reading activities, a child can explore himself. However, in reality on the ground, low interest in reading is still a problem that is often found today. Children's interest in reading in Indonesia is included in a worrying category. Kancana Village is one of the areas in Cikijing District where reading interest must be increased. Facilities and infrastructure are needed that can accommodate children in reading activities. Therefore, the presence of the Reading Corner in this Real Work Lecture (KKN) activity is a bridge to foster children's interest in reading in Kancana Village. Apart from fostering interest in reading, this reading corner activity program can improve children's linguistic, psychomotor and social abilities.